Main features of the modern environmental agenda of the Alternative for Germany - A. D. Lisenkova (Управленческое консультирование)
This article is devoted to the environmental agenda of the national party Alternative for Germany. The main features of this agenda’s development are being analyzed through its federal and European election programmes from 2013 to 2021. First of all, the author defines the specifics of the party’s evolution outside the environmental context to demonstrate the gradual enlargement of the spheres of party interests and the transition from an exclusively economically oriented liberal conservative Eurosceptic course to far-right and populist, anti-immigration and Islamophobic tendencies. Then the article illustrates the important role of the common European environmental context, where actions to combat climate change are getting more prioritized. This is reflected in the new course for the Alternative for Germany, aimed at denying the advisability of climate measures in Germany and the European Union. The latter has leadership ambitions in the global political arena in the fight against climate change and the high popularity of this environmental topic is among voters. It’s the reason why climate change was coming to the fore in the party’s populist rhetoric. At the same time, the author questions the possibility of near-term environmental and, above all, climate or even anti-climate coordination between the Alternative for Germany and ideologically similar partner parties in the Identity and Democracy group of the European Parliament.